Sustainable intensification of mixed farming system in West Africa: concepts, practices, and challenges - Igbadun, H. E.; Ojeleye, O. A.; Mabhaudhi, T.; Cofie, Olufunke O. (Springer, 2025)
Sustainable intensification (SI) is a system of production that increases output without causing significant environmental damage. It focusses on enhancing agricultural land production while managing its environmental impact. Evaluation frameworks have evolved to include non-environmental aspects, such as social concerns, economics, and the human condition. Agricultural sustainability assessment now uses indicator frameworks, which are structured into five domains: productivity, economic, environment, the human condition, and social domains. Mixed farming systems (MFS) is an approach to sustainable agriculture where farmers produce crops and animals in the same location under the same ownership. MFS provides enough food for consumers and income for farmers while ensuring soil fertility, biodiversity, and pest control. Several characterizations and typologies of MFS in West Africa have been identified, but the level of development varies due to farmers’ preferences. Despite the benefits of MFS, socio-economic factors, such as skills and competencies, the role of the agricultural knowledge and innovation system, the economy, and the policy environment, pose major challenges and obstacles to its growth in West Africa.